The Stories and Meanings Behind the Higaunon Traditional Dance: Dinugsu/Dugsu - Mary Jean Taclindo-Palabrica (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
: This study aims to reveal the stories and meanings behind the selected Higaunon traditional dance known as Dinugsu/Dugsu, so as to save and preserve the dance history and its forms of this particular tribe, and its cultural tradition and heritage in general. It aims to identify themes behind the selected traditional dance as a way of saving and preserving its history and forms. This is in pursuant to UNESCO’s standpoint of maintaining, safeguarding, and preserving intangible heritage. This study utilizes a descriptive evaluative research design. The stories and meanings behind the selected Higaunon traditional dance are revealed. Also, a semi-structured interviews are done with the practitioners or the performers of the traditional dance in focused. this assisted in the giving of meanings behind each of the stories of the dance. Interviewees are selected based on their level of mastery and expertise within their traditional dances. These experts are selected out from their indigenous community. Results of this study present four relevant themes on the selected traditional dance. The themes are namely: prayer, unity, thanksgiving, and offering for blessing.